Respon Australia Atas Jepang Pasca Mengeluarkan kebijakan JARPA II tahun (2005-2011) - Lidya Adristhira; Yusnarida Eka Nizmi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research will explain about the Response of Australia Post Japan’s JARPA II policy in2005-2011. Antarctic is the biggest whale population region. In 2005, the government of Japan issuedthe policy of Second Phase of the Japanese Whale Research Program under Special Permit inthe Antarctic (JARPA II). The important point of this research is Japan is one of the countrywhich supports anti-whaling moratorium commercial but on the other hand Japan issuedpolicy of pro-whaling through Scientific Whaling program. This policy causes the refusal ofAustralian government. This refusal relates to maritime security and environmentalprotection efforts in Antarctic region.Keywords: Sceientific whaling, Australia’s refusal, maritime security, Antarctic